Waves in the sky: Probing the ionosphere with the Murchison Widefield Array - Loi, S.; Murphy, T.; Cairns, I.; Trott, Cathryn; Bell, M.; Hurley-Walker, Natasha; Morgan, John; Lenc, E.; Offringa, A.; Menk, F.; Waters, C.; Feng, L.; et al. (2015)
© 2015 International Union of Radio Science (URSI). Low-frequency, wide-field radio telescopes such as the Murchison Widefield Array (MWA) enable the dense spatial sampling of the ionosphere and plasmasphere on regional scales. For a physically compact array such as the MWA, the refractive shifts in the positions of celestial sources in the synthesised radio images are proportional to spatial gradients in the total electron content (TEC) transverse to the line of sight. By measuring the angular position shifts of celestial radio sources, one can probe waves and disturbances in the intervening plasma. Radio telescopes differ fundamentally from other techniques for measuring plasma fluctuations in that they are sensitive to TEC gradients/differences rather than absolute TEC. This makes them sensitive specifically to fluctuations about the ambient density, and therefore powerful probes of plasma density waves and irregularities.